TI_GERICHTE 90.2013.3 vom 12. November 2014 , Conferma di vincoli per un fondo inserito in zona di pericolo valangario - TI Tribunale d'appello (2014)
Conferma di vincoli per un fondo inserito in zona di pericolo valangario